Spontaneous intersibling polymorphism in the development of dopaminergic neuroendocrine cells in sea urchin larvae: impacts on the expansion of marine benthic species - Obukhova, Alexandra L.; Khabarova, Marina Yu.; Semenova, Marina N.; Starunov, Viktor V.; Voronezhskaya, Elena E.; Ivashkin, Evgeny G. (Frontiers in Neuroscience, 2024)
Introduction The plasticity of the nervous system plays a crucial role in shaping adaptive neural circuits and corresponding animal behaviors. Understanding the mechanisms underlying neural plasticity during development and its implications for animal adaptation constitutes an intriguing area of research. Sea urchin larvae offer a fascinating subject for investigation due to their remarkable evolutionary and ecological diversity, as well as their diverse developmental forms and behavioral patterns. Materials and methods We conducted immunochemical and histochemical analyses of serotonin-containing (5-HT-neurons) and dopamine-containing (DA-positive) neurons to study their developmental dynamics in two sea urchin species: Mesocentrotus nudus and Paracentrotus lividus. Our approach involved detailed visualization of 5-HT- and DA-positive neurons at gastrula-pluteus stages, coupled with behavioral assays to assess larval upward and downward swimming in the water column, with a focus on correlating cell numbers with larval swimming ability. Results The study reveals a heterochronic polymorphism in the appearance of post-oral DA-positive neuroendocrine cells and confirms the stable differentiation pattern of apical 5-HT neurons in larvae of both species. Notably, larvae of the same age exhibit a two- to four-fold difference in DA neurons. An increased number of DA neurons and application of dopamine positively correlate with larval downward swimming, whereas 5-HT-neurons and serotonin application induce upward swimming. The ratio of 5-HT/DA neurons determines the stage-dependent vertical distribution of larvae within the water column. Consequently, larvae from the same generation with a higher number of DA-positive neurons tend to remain at the bottom compared to those with fewer DA-positive neurons. Discussion The proportion of 5-HT and DA neurons within larvae of the same age underlies the different potentials of individuals for upward and downward swimming. A proposed model illustrates how coordination in humoral regulation, based on heterochrony in DA-positive neuroendocrine cell differentiation, influences larval behavior, mitigates competition between siblings, and ensures optimal population expansion. The study explores the evolutionary and ecological implications of these neuroendocrine adaptations in marine species.